Surgical treatment of drug resistant epilepsy in Sturge-Weber syndrome: review of the literature and clinical case presentation - G. S. Ibatova; S. K. Akshulakov; S. M. Malyshev; R. G. Khachatryan; T. M. Alekseeva; A. S. Shershever; W. A. Khachatryan (Эпилепсия и пароксизмальные состояния)
The paper addresses the relatively rare inherited neurodermal disorder – Sturge-Weber syndrome that can manifest in epileptic seizures. We describe updated concepts, epidemiology, etiology, pathogenesis, clinical manifestations, and surgical treatment of the disease. We examined medical records of 21 patients (aged from 1 to 11 years) with Sturge-Weber syndrome treated over the period of 1996-2016. After surgical treatment of 10 patients (five cases with hemispheretomy and five – with multifocal resection), positive outcomes (Engel class I, II) were found in 70% of cases, and negative (Engel class III, IV) – in 20% of cases. Оne child suddenly died during epileptic seizures. In non-operated children (age from 2 to 5 years) under our observation, an improvement was noted in six cases, no changes – in three cases, and a further progression of the disease – in three cases. In this article, we analyze two of these cases in detail.